Kepatuhan Syariah dalam Implementasi Pembiayaan Tabarok dengan Akad - Sopian Hanapi; Holilur Rahman (Assyarikah: Journal of Islamic Economic Business, 2025)
This study aims to examine the implementation of Tabarok financing using the mu??rabah contract and to identify the factors influencing its Sharia compliance at PT. BPRS Sarana Prima Mandiri Pamekasan. The focus of the study is directed toward assessing the conformity of financing practices with Sharia principles, considering the distinctive characteristics of the Tabarok product, which applies a daily installment system and a door-to-door marketing strategy that may lead to variations in implementation in the field. This research adopts a qualitative approach with a descriptive method, employing interviews, observations, and documentation as data collection techniques, while data validity is ensured through source triangulation. The findings indicate that Tabarok financing is implemented under a mu??rabah scheme, in which the bank acts as the ???ibul m?l (capital provider) and the customer as the mu??rib (entrepreneur), with a flexible daily installment mechanism adjusted to the customer’s business capacity. The One Day One Street marketing strategy is applied to bring financing services closer to micro-entrepreneurs while simultaneously expanding Islamic financial inclusion. Sharia compliance in Tabarok financing is influenced by several key factors, including customer selection and eligibility assessment, Sharia education related to mu??rabah principles, active supervision by the Sharia Supervisory Board, and continuous financing monitoring. The study concludes that the implementation of Tabarok financing complies with Sharia principles in terms of contractual structure, fund management mechanisms, and supervisory processes. This research contributes to enriching empirical studies on mu??rabah-based financing practices in Islamic rural banks (BPRS), particularly microfinance products utilizing daily installment systems and direct community-based marketing approaches.